A comparison of curricula at various medical schools across the world - Zawiślak, Dorota; Kupis, Robert; Perera, Ian; Cebula, Grzegorz (Folia Medica Cracoviensia, 2023)
Background: Medical education has changed in response to scientific advances and social needs. Aim: The aim of the study was to examine curricula of medical schools around the world and to observe the trends that currently dominate in medical education. Method: We have collected information on the current curricula of various medical schools using their official websites. When necessary, we supplemented the information using published articles describing the curriculum of a given medical school. Results: Our findings reveal that medical schools demonstrate the need for constant reforms and adaptation to changing conditions worldwide. Generally, there is a tendency to integrate basic and clinical fields, to sooner establish bedside teaching, to provide less theoretical and more practical approaches to teaching, to implement more communication skills, and provide students with research training. Conclusions: Medical education has evolved and will continue to change with time. Medical schools introduce modifications to their curricula and share their experiences.
Keywords: curriculum; medical program; medical schools; undergraduate